2004
DOI: 10.1111/j.1471-6712.2004.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic strain: a hindrance in rehabilitation?

Abstract: Long-term sick leave due to musculoskeletal disorders has increased, especially for women. The aim of this paper was to explore women's and men's descriptions of the private arena in relation to rehabilitation and sickness absence. This study is part of a larger project focusing on consequences of sick leave. Individual interviews were conducted in 1997 and 1998 with 20 women and men who had been long-term sick-listed in 1985 with musculoskeletal diagnoses. The data were analysed using Grounded theory in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…This result was in line with the two earlier studies on psychological distress, which found inequity in division of domestic work to be a greater contributory factor to women's psychological distress than the amount of domestic work [10,11]. The importance of a confident relationship with a partner for women's psychological health has also been revealed in the work of Brown and Harris [27] and with findings in the qualitative study by Ö stlund et al [12]. The associations could go either way: physical or mental health problems might contribute to general strain in the relationship and to marital conflicts, conversely, low marital satisfaction and perceived inequity in the division of domestic workload could also be involved in the development of physical and mental health problems.…”
Section: Importance Of the Relationship With Spouse/cohabiter And Persupporting
confidence: 92%
“…This result was in line with the two earlier studies on psychological distress, which found inequity in division of domestic work to be a greater contributory factor to women's psychological distress than the amount of domestic work [10,11]. The importance of a confident relationship with a partner for women's psychological health has also been revealed in the work of Brown and Harris [27] and with findings in the qualitative study by Ö stlund et al [12]. The associations could go either way: physical or mental health problems might contribute to general strain in the relationship and to marital conflicts, conversely, low marital satisfaction and perceived inequity in the division of domestic workload could also be involved in the development of physical and mental health problems.…”
Section: Importance Of the Relationship With Spouse/cohabiter And Persupporting
confidence: 92%
“…Even so, they often feel guilty for spending too little time with their children [6,28]. This corresponds to the accounts given by our own interviewees.…”
Section: Mothers and Time Todaymentioning
confidence: 58%
“…However, research on work-family conflicts has so far primarily focused on perceived imbalances between work and family life without distinguishing between different sources to this imbalance (20). Only few studies have investigated the combined effect of work and family factors on sickness absence (21)(22)(23)(24). Two studies, based on the same occupational cohort, showed that the combination of high work and family demands predicted all-cause sickness absence and sickness absence due to mental health disorders (21,22).…”
mentioning
confidence: 99%